ANALYSIS OF THE TEACHING PROCESS OF BALLROOM DANCE IN BELO HORIZONTE - MG (Fiep Bulletin - online, 2012)
The Ballroom Dance is increasingly present in society. Currently considered fashionable, it arouses the interest of a broad audience. Nowadays, it is practiced as a form of entertainment, physical activity and even with therapeutic purposes. One of the main concerns of Ballroom Dance teachers is to develop a methodology that meets the needs and is suitable to the characteristics of practitioners. The present study aims to analyze the process of teaching of Ballroom Dancing in dance schools of Belo Horizonte. This research was comprised of a sample of 16 teachers of Ballroom Dancing from 8 dance schools of Belo Horizonte. Based in the questionnaires applied and literature used, it was possible to observe as the most meaningful result to the process of teaching of Ballroom Dance, only a reproduction of the format and methods of classes of other professionals and the need to develop specific methodologies for teaching of Ballroom Dance.
Keywords: Dance; teaching; methodology